2021
DOI: 10.1051/e3sconf/202126801028
|View full text |Cite
|
Sign up to set email alerts
|

Research on the effect of different test cycles on low temperature emissions and fuel consumption of Light plug-in hybrid cars

Abstract: Based on a plug-in hybrid car equipped with a 1.5L turbocharged direct injection gasoline engine, this paper studies the emission and fuel consumption characteristics of the prototype vehicle under three different cycle conditions, WLTC city, WLTC and CLTC-P. The results show that for the four pollutants: CO, THC, NMHC and NOx, WLTC city cycle emissions are the largest, WLTC cycle emissions are the smallest, CLTC-P cycle emissions are the middle. For N2O, WLTC cycle has the largest combined emissions, CLTC-P c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The results of [28] In [24], typical dynamic conditions of vehicle motion in WLTC [3,9] were studied in order to simulate the emission of particulate matter from tribological pairs in a vehicle.…”
Section: State Of Current Knowledgementioning
confidence: 99%
“…The results of [28] In [24], typical dynamic conditions of vehicle motion in WLTC [3,9] were studied in order to simulate the emission of particulate matter from tribological pairs in a vehicle.…”
Section: State Of Current Knowledgementioning
confidence: 99%
“…Wang et al (2020b) found that fuel consumption between WLTC and RDE was at the same level, while the fuel consumption of CLTC-P was 8.41% higher than that of WLTC. Some studies (Geng et al 2021;Ma et al 2021;Yang et al 2021) also have investigated the emission characteristics of different emission control technology routes under the CLTC-P. However, there is still a lack of a large number of test research on CLTC-P, and a uni ed method for quantitatively evaluating CO 2 emissions measured under different test cycles is yet to be established.…”
Section: Introductionmentioning
confidence: 99%